FOREIGN EXPERIENCE IN PROFESSIONAL TRAINING OF SPECIALISTS IN THE FIELD OF BUSINESS TOURISM MANAGEMENT - Fazilat Sodiqovna, Rakhmonova (IJBLE Scientific Publications Community Inc., 2022)
The rapid pace of development of the tourism industry in Uzbekistan has led to the emergence of many tourist educational institutions involved in training personnel for work in tourism. However, the level of training of specialists in many aspects does not meet modern requirements, including the professional training of specialists in business tourism management. The tourism industry needs qualified personnel, but training a competent professional in business tourism management is low. The article explored the foreign experience of professional training specialists in business tourism management and studied how this area can be used in Uzbekistan universities and the results of this stage